The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-3016.2012.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiple Micronutrient Supplementation on Pregnancy and Infant Outcomes: A Systematic Review

Abstract: Supplementation with multiple micronutrients (MM) during pregnancy may result in improved pregnancy and infant outcomes. We conducted meta-analyses of randomised controlled trials that evaluated the effects of prenatal supplementation with MM (defined as containing at least five micronutrients and typically included iron or iron and folic acid). The outcomes of interest were low birthweight (<2500 g), birthweight, small-for-gestational age (SGA), gestational age, preterm birth (<37 weeks' gestation), stillbirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 40 publications
17
90
3
5
Order By: Relevance
“…Birth outcomes have been assessed in another paper in this supplement. 33 Continuous data were pooled to get a standard mean difference. Dichotomous data were pooled to get a relative risk, which was reported along with 95% CI.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth outcomes have been assessed in another paper in this supplement. 33 Continuous data were pooled to get a standard mean difference. Dichotomous data were pooled to get a relative risk, which was reported along with 95% CI.…”
Section: Data Analysesmentioning
confidence: 99%
“…27 Some MMN supplementation studies have also suggested benefits on infant 28 and newborn mortality 29 and growth in later infancy. 30 Others have cautioned against the use of these supplements on the basis of an increased risk of perinatal mortality observed in some settings [31][32][33] although this has been disputed given the overall variation in context. 18,26 In the current conundrum an evaluation of the potential benefits and risks of replacing iron folate supplements with MMN is necessary and must in the first instance be based on a factual evaluation of the scientific benefits and risks.…”
mentioning
confidence: 99%
“…Особенно неблагоприятны дефициты микро-нутриентов для беременных женщин, поскольку отсутствие или недостаток микронутриентов имеют программирующее воздействие на здоровье ребёнка и будущего поколения [9]. Ещё в 1932 г. Ф. Хэйл опу-бликовал исследования по дефицитному по витамину А рациону питания свиней на ранних сроках зачатия.…”
Section: Hygieneunclassified
“…Folic acid has long been acknowledged as influential nutrient pre and during pregnancy to prevent neural tube defect 7,11 . Inadequate intrauterine nutrient supply brings information of adverse life conditions in the extra-uterine environment; it may enable to re-program metabolic pathways of the growing conceptus to prepare it to the shortage of food in later life.…”
Section: Insuline Restrictionmentioning
confidence: 99%